Current nonclinical approaches for immune assessments of immuno-oncology biotherapeutics. Issue 2 (February 2023) - Grimaldi, Christine; Ibraghimov, Alex; Kiessling, Andrea; Rattel, Benno; Ji, Changhua; Fuller, Claudette L.; Brennan, Frank R.; Regenass-Lechner, Franziska; Shenton, Jacintha; Price, Karen D.; Piché, Marie-Soleil; Steeves, Meredith A.; et al.
Highlights: Cancer immunotherapy is associated with immune-related adverse events. Current nonclinical approaches for assessment of these adverse events are reviewed in this manuscript. Approaches for first-in-human starting doses are discussed. Abstract : Harnessing the immune system to kill tumors has been revolutionary and, as a result, has had an enormous benefit for patients in extending life and resulting in effective cures in some. However, activation of the immune system can come at the cost of undesirable adverse events such as cytokine release syndrome, immune-related adverse events, on-target/off-tumor toxicity, neurotoxicity and tumor lysis syndrome, which are safety risks that can be challenging to assess non-clinically. This article provides a review of the biology and mechanisms that can result in immune-mediated adverse effects and describes industry approaches using in vitro and in vivo models to aid in the nonclinical safety risk assessments for immune–oncology modalities. Challenges and limitations of knowledge and models are also discussed.